Estudo das comunidades bacterianas em filtros biológicos percoladores utilizados para o pós-tratamento de efluentes de um reator UASB - Beatriz de Souza Missagia (2010)
The aim of this study was to investigate the influence of environmental conditions provided by four different types of packing media, distinct depths and two different organic loading rates (OLR) on bacterial diversity, and abundance, distribution of nitrifying bacteria, as wellas on reactor performance (ammonia removal) in four trickling filters following UASB reactors treating domestic wastewater. Microorganisms of various complexities and functions were viewed, and the top of the FBP showed the highest diversity of morphologies, due to the increased availability of organic matter, sunlight and oxygen at this point. The significant increase in the number of Nitrobacter cells were detected from the middle to bottom of all TF, in both phases of operation (OLR of 0.24 and 0.38 kgBOD/m3.d), in accordance with the high nitrate concentrations and low concentrations of BOD also found in this portion of the filters.However, the abundance of cells of AOB and Nitrospira remained constant. The different compositions and configurations of packing media provide different environmental conditions, leading to the development of different profiles of distribution and abundance of Bacteria, AOB and NOB and Thiobacillus denitrificans, and the DHS system showed thehighest abundance of all organisms investigated in the two phases of operation. The interstitial spaces of the DHS are ideal for the biomass retention and also the available substrates, resulting in favourable environmental conditions to nitrification. Bacteria counts were significantly higher in the OLR of 0.38 kgBOD/m3.d., while there was a significantdecrease in the nitrifying bacteria amount in all the TF. These aspects are consistent with the low ammonia removal observed in the operational phase with higher OLR. The increase in OLR promoted the appearance of anoxic and anaerobic microenvironments. These environmental conditions were decisive for the development of T. denitrificans in DHS and plastic tubing. Although the reactors were fed with the same effluent from the UASB reactor, the different compositions and configurations of the packing medias resulted in the development of different environmental conditions that lead to the development of diversespecies. Actinobacteria, Firmicutes and the clone UTFs-R12-90-53 (uncultivated) were identified in biofilm samples with more than 98% similarity with sequences deposited at NCBI from DHS systems and an aerobic / anaerobic domestic wastewater treatment.